Changes in Pectic Substances and Cell Wall Degrading Enzymes During Muskmelon Fruit Ripening (University of Khartoum Journal of Agricultural Sciences, 2023)
Changes in pectic substances and the activities of the cell walldegrading enzymes, pectin esterase (PE) and polygalacturonase (PG) wereevaluated during muskmelon fruits ripening. Respiration rateprogressively increased in a climacteric pattern. Fruit flesh firmnesssteadily declined and rind yellow colour increased during ripening. Totaland insoluble pectins progressively decreased, while the soluble pectinsincreased with fruit ripening. Positive correlation coefficients wereobtained between total and insoluble pectins, and fruit flesh firmness.Total protein and PE activity increased up to the climacteric peak ofrespiration and decreased afterwards. PG activity progressively increasedduring fruit ripening, with high correlation between the increase inenzyme activity and fruit softening in the three muskmelon cultivars. Thismay indicate that the two enzymes polygalacturonase (PG) and pectinesterase (PE) are the main enzymes responsible for fruit softening duringmuskmelon fruit ripening.
Keywords: Muskmelon frui; pectic substances; pectin esterase (PE)